2001
DOI: 10.1097/00000542-200112000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation Anesthetics Induce Apoptosis in Normal Peripheral Lymphocytes In Vitro 

Abstract: Both sevoflurane and isoflurane induced apoptosis in peripheral lymphocytes in dose-dependent and time-dependent manners in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
98
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(104 citation statements)
references
References 0 publications
3
98
1
2
Order By: Relevance
“…Lymphocytes seemed to respond to isoflurane with early (within 4 hours) recruitment into the bone marrow, whereas surgical stress caused a marked increase in bone marrow myeloid cells 72 hours after surgery. Volatile anaesthetics reportedly affect leukocyte responses; e.g., they alter neutrophil adherence to blood vessels (Heindl et al, 1999), induce apoptosis of lymphocytes (Matsuoka et al, 2001), or affect the resolution of inflammation (Chiang et al, 2008). They also contribute to ischaemic brain injury (Lee et al, 2007;Li and Zuo, 2009), but our results are the first to show that both surgery and anaesthesia interact with experimental stroke to cause cellular and cytokine changes directly in the bone marrow.…”
Section: Discussionmentioning
confidence: 62%
“…Lymphocytes seemed to respond to isoflurane with early (within 4 hours) recruitment into the bone marrow, whereas surgical stress caused a marked increase in bone marrow myeloid cells 72 hours after surgery. Volatile anaesthetics reportedly affect leukocyte responses; e.g., they alter neutrophil adherence to blood vessels (Heindl et al, 1999), induce apoptosis of lymphocytes (Matsuoka et al, 2001), or affect the resolution of inflammation (Chiang et al, 2008). They also contribute to ischaemic brain injury (Lee et al, 2007;Li and Zuo, 2009), but our results are the first to show that both surgery and anaesthesia interact with experimental stroke to cause cellular and cytokine changes directly in the bone marrow.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, it has been reported that NK activity decreases and that the reactivity between NK cells and interferon-γ is suppressed after anesthesia in humans [5]. Third, there may be a direct action of isoflurane on lymphocytes, because a decrease in NK cytotoxic activity has been reported in an ex vivo experiment in which human lymphocytes were exposed to isoflurane [8]. However, it has also been reported that the site of the cytotoxic action of isoflurane on lymphocytes is not the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…For example, isoflurane decreases cytokine production in lymphocytes and NK cell activity [7] and can also induce apoptosis of lymphocytes [8]. To our knowledge, effects of anesthetics on anti-tumor immunity have not been reported for veterinary medicine.…”
mentioning
confidence: 98%
“…It was shown that the induction of apoptosis is accompanied by increased levels of activated caspase-3 (CASP3) in the analyzed lymphatic cells (43). At the same time, it was shown that isoflurane limphotoxicity was greater than sevoflurane limphotoxicity.…”
Section: The Impact Of Volatile Anaesthetics On the Function Of Lymphmentioning
confidence: 95%
“…In vitro, isoflurane and sevoflurane directly induce the phenomenon of apoptosis in human peripheral blood lymphocytes depending on a dose and the duration of exposure (43).…”
Section: The Impact Of Volatile Anaesthetics On the Function Of Lymphmentioning
confidence: 99%